Optimalisasi Hasil Belajar Peserta Didik Mapel Informatika Materi Sistem Komputer Melalui Model project Based Learning metode Demontrasi di Kelas X.10 SMAN 1 Lareh Sago Halaban - Safitri, Fidiyah Rahma; Zakir, Supratman; Herman, Ekoza Yupino (Indonesian Research Journal on Education, 2023)
This study aims to determine the effect of the Project Based Learning model on Informatics learning outcomes in class X.9 SMAN Lareh Sago Halaban. This research was conducted using a quasi-experimental approach, using a non-equivalent control group design. Information collection methods used are tests and observations. The results showed that there was a significant influence on the learning outcomes of Informatics through a project-based learning model in class X.9 SMAN 1 Lareh Sago Halaban. This is in line with the advantages of the Project Based Learning model, namely; 11) improve problem solving skills, 2) improve cooperation, 3) increase motivation, 4) improve resource management skills, 5). improve resource management skills as well.